2004
DOI: 10.1038/sj.onc.1208358
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of KIT and platelet-derived growth factor receptor α mutations with gene activation and expression profiles in gastrointestinal stromal tumors

Abstract: Activating mutations of KIT and platelet-derived growth factor receptor a (PDGFRA) are known to be alternative and mutually exclusive genetic events in the development of gastrointestinal stromal tumors (GISTs). We examined the effect of the mutations of these two genes on the gene expression profile of 22 GISTs using the oligonucleotide microarray. Mutations of KIT and PDGFRA were found in 17 cases and three cases, respectively. The remaining two cases had no detectable mutations in either gene. The mutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 34 publications
4
94
1
2
Order By: Relevance
“…1,10 -12 GISTs in these families are characterized by development at multiple primary sites and presentation at a median age of 46 years; polyclonal diffuse hyperplasia of ICCs within the myenteric plexus is considered the primary effect of KIT constitutive activation. 10,22,23 Other abnormalities may be present in patients with familial GISTs: for example, patients with germline KIT exon 11 mutations often show cutaneous hyperpigmentation in the perineum, face, neck, digits, axillae, groin and knees and less frequently urticaria pigmentosa or diffuse cutaneous mastocytosis in infancy. 10,23 Patients with germline PDGFRA mutations present with multiple gastric GISTs or the condition known as intestinal neurofibromatosis.…”
Section: Discussionmentioning
confidence: 99%
“…1,10 -12 GISTs in these families are characterized by development at multiple primary sites and presentation at a median age of 46 years; polyclonal diffuse hyperplasia of ICCs within the myenteric plexus is considered the primary effect of KIT constitutive activation. 10,22,23 Other abnormalities may be present in patients with familial GISTs: for example, patients with germline KIT exon 11 mutations often show cutaneous hyperpigmentation in the perineum, face, neck, digits, axillae, groin and knees and less frequently urticaria pigmentosa or diffuse cutaneous mastocytosis in infancy. 10,23 Patients with germline PDGFRA mutations present with multiple gastric GISTs or the condition known as intestinal neurofibromatosis.…”
Section: Discussionmentioning
confidence: 99%
“…When expressed in transfected cell lines, mutant forms of PDGFRA have constitutive kinase activity in the absence of their ligand, PDGF-A, 37,38 the activated downstream pathways are identical to those in KIT-mutant GISTs, 37,39 and PDGFRA is also stabilized by HSP90. 40 In addition, both types of tumors are immunopositive Figure 3 (a) KIT and PDGFRA cell signaling pathways.…”
Section: Platelet-derived Growth Factor Receptor-amentioning
confidence: 99%
“…Although KIT exon 11 mutations have been reported in GISTs from different locations from esophagus to anus, [105][106][107][108][109][110][111][112] duplications showed strong predilection to gastric location; 59 of 67 (88%) reported GISTs with KIT exon 11 duplications originated from stomach. 61,74,76,77,83,84,97,101,113 …”
Section: Kit Regulatory Domain Mutations (Exon 9 Exon 11)mentioning
confidence: 99%
“…74,81,101 Technical problems limiting detection of duplications in FFPE tissues may contribute to this discrepancy, since other studies from Korea and China have been reported KIT exon 11 duplications in GISTs. 83,84,99,100 …”
Section: Frequency Of Kit and Pdgfra Mutationsmentioning
confidence: 99%